Design and synthesis of new bioisosteres of spirooxindoles (MI-63/219) as anti-breast cancer agents. Issue 4 (15th February 2015) - Kumar, Atul; Gupta, Garima; Bishnoi, Ajay Kumar; Saxena, Ruchi; Saini, Karan Singh; Konwar, Rituraj; Kumar, Sandeep; Dwivedi, Anila
Graphical abstract: Abstract: We report herein the design and synthesis of bioisosteres of spirooxindole (MI-63/219), a small-molecule inhibitors of the MDM2–p53 interaction as anti-breast cancer agents. Compound5b has been exhibiting significant anti-proliferative activity in nude mice bearing MCF-7 xenograft tumor. The compound5b was found to act via modulation of MDM2 and p53 expression in breast cancer cells expressing wild type p53. Compound5b stimulated p53 activation, caused modulation of downstream effectors p21, pRb, and cyclin D1 which regulate cell cycle. Thus, compound triggered G1–S phase cell cycle arrest, which was evident by flow cytometric analysis of treated breast cancer cells. Thus, compound5b restores the p53 function, which triggers molecular events consistent with cell cycle arrest at G1/S phase.